First record of Morimotobathynella Serban, 2000 (Bathynellacea, Bathynellidae) from subterranean waters of South Korea, with the description of a new species - Su-Jung Ji; Ana Isabel Camacho; Gi-Sik Min (ZooKeys)
This study describes Morimotobathynella koreana sp. nov., the first new species of Bathynellidae family reported in East Asia since 2000, and it presents the first molecular analysis using CO1 and 18S gene sequences. Morphological analysis reveals that the new species and previously known Morimotobathynella species uniquely share key characteristics in the male and female thoracopods VIII. However, the presence or absence of the median seta on the antenna exopod, along with the length differences between the four spines in the furca, distinguish the new species from M. miurai, 2000. A molecular phylogenetic analysis indicates that the new species has a relatively close relationship to species from the genus Altainella in Mongolia and Russia.